A fixed point theorem for a pair of maps satisfying a general contractive condition of integral type - P. Vijayaraju (International Journal of Mathematics and Mathematical Sciences, 2005)
We give a general condition which enables one to easily establish fixed point theorems for a pair of maps satisfying a contractive inequality of integral type.